Digitization of the Dinar Amanta Sidoarjo Cooperative through the KOPERKU Application to Support Asta Cita and SDGs - Nur Ravita Hanun; Andry Rachmadany; Denisa Iselina Suwandono; Rosmawati Andriani Utami (Bubungan Tinggi: Jurnal Pengabdian Masyarakat, 2026)
This program aims to enhance the financial management of the Dinar Amanta Cooperative through the KOPERKU application. Employing a Participatory Action Research (PAR) framework, the program combined structured training and business mentoring, actively engaging cooperative members as co‑designers of the intervention. The intervention introduced an information‑based financial system, replacing manual bookkeeping with the KOPERKU Application Usage Module. Quantitative analysis revealed a 100 % increase in financial accuracy, transparency, and accountability, while qualitative feedback underscored heightened member confidence and sustained knowledge retention. The findings demonstrate that participatory mentoring, coupled with a tailored digital tool, can effectively drive digital transformation in cooperative settings. These results suggest that similar interventions may be replicated in other cooperatives to foster sustainable, data‑driven financial practices.